Pemanfaatan Ikan Red Devil (Amphilophus labiatus) sebagai Pupuk Organik Cair dan Produk Pangan Olahan di Sekitar Danau Toba - Grace Happy Hotmauli Simbolon; Leonard Dharmawan; Edi Wiraguna (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Lake Toba, designated as a National Tourism Strategic Area, faces ecological disruption due to the invasive Red Devil fish (Amphilophus labiatus), which threatens the sustainability of native aquatic species. This study aims to enhance the knowledge of the Tapian Nauli farmer group in Hariara Pohan Village, Samosir Regency, in utilizing the Red Devil fish as Liquid Organic Fertilizer (LOF) and processed food. Methods employed include agricultural extension activities, practical demonstrations, pre-tests and post-tests, and evaluation through questionnaires. Results showed a significant improvement in farmers' knowledge after the extension, with 70% moving from the